ANALISA SISTEM KERJA MEJA DAN KURSI LIPAT UNTUK LUAR RUANG - Mulyadi Mulyadi (Narada : Jurnal Desain dan Seni, 2021)
Everyone's need for household furniture and limited space are problems that often occur in the middle to lower economic class. This is a concern for designers to create a solution in making practical household furniture, one of which is folding tables and chairs that save space and can be carried everywhere. Folding tables and chairs for outdoor is a table and chairs that can be placed for the outdoors and can be folded and can be carried anywhere. In this case, the author describes the work system and the benefits of folding tables and chairs. The analysis result, that explain things that must be considered in making folding tables and chairs include material, ergonomics, shape, work environment, and people. Then the research was carried out on one of the folding table and chair products called the Hobbit. The author examines the work system of the folding tables and chairs, starting from the materials or materials used, the size, how to use them, namely opening and closing the folds, as well as testimonials from correspondents who have tried using the product. Overall, the function of folding tables and chairs for outdoor can be more practical, because if they are not used, folding tables and chairs can be stored so that they save storage space and can be placed as you wish.